EVALUATION OF IN VITRO ANTHELMINTIC PROPERTIES OF AVICENNIA MARINA LEAVES - Kondepudi, Gana Manjusha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objectives: The purpose of the present study was to determine the anthelmintic properties of chloroform, methanol and aqueous extracts of Avicennia marina leaves on Indian earthworm- Pheretima posthuma. Methods: Three concentrations of each extract (25 mg/ml, 50 mg/ml, and 75 mg/ml) were studied in this activity to determine the time of paralysis (vermifuge) and the time of the death of the worms (vermicidal). Piperazine citrate in the same concentrations was taken a reference standard and normal water was taken as control. The time taken for paralysis and death of the worms was recorded. Results: All the extracts showed dose-dependent and a significant activity was shown at higher concentration (75 mg/ml). Methanolic extract showed peak activity at a concentration of 75 mg/ml. Conclusion: Based on the results it was found that the leaves of A. marina possess vermifuge and vermicidal activities and can be used as an effective anthelmintic.